Pemasaran dan Keuangan Digital untuk Tingkatkan Pendapatan Usaha Batik di Desa Srowot - Winarni, Dwi; Fakhruddin, Iwan; Kusbandiyah, Ani (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Srowot Village in Banyumas Regency has a promising group of batik artisans but still faces challenges in marketing and financial record-keeping. This community service activity aims to increase income and business sustainability through training in digital marketing and digital financial recording. The methods used include training on the use of social media and e-commerce platforms, branding strategies, and financial recording using simple applications such as Google Sheets or similar tools. The activity also involved students and lecturers from various fields as facilitators and companions during implementation. The results show that members of the group have begun to understand the benefits of digital marketing; several have created business accounts and started recording transactions digitally. However, challenges remain in managing promotional content, maintaining consistent financial records, and dealing with limited devices and poor internet access. In conclusion, training and mentoring have significantly improved the group’s digital capacity, but continued strategies, accessible educational materials, and sustained assistance are needed to ensure optimal and consistent implementation over the long term.